Reflection of Teacher’s Interpersonal Skill: Describing The Quality of An Effective Teacher - Hastowohadi Hastowohadi (Department of English Language Education, UIN Sunan Ampel Surabaya, 2017)
There are six characteristics that can not be taught, only modeled, they are Caring, Fairness and Respect, Attitude toward the Teaching Profession, Social Interaction with Students, Promotion of Enthusiasm and Motivation for Learning, Reflective Practice. The aspect of teacher as a person is only one of six aspects that should be modeled and demonstrate to the students. But, this aspect is going to be left by teachers in this era. It will be monotonous teacher as a leader and messenger in holding the whole class of teaching-learning activity. Furthermore, in this research, the writer wants to explore and find out what are actually the problems of this issue. The research was done in SMK Visi Global in Banyuwangi and took 6 teachers as an object of research. The writer used descriptive qualitative and describing the phenomenon of this. Indeed, the result was Fairness and Respect, Attitude toward Teaching Profession, Enthusiasm, and Motivation for Learning, and Reflective Practice got above average but Caring, Social Interaction with Students got below average. This issue described that the teachers in SMK Visi Global were not enlightened by a good teacher as a person and it would be ineffective for the school and students itself. It can be concluded that preparing teacher?s personality is unavoidable for the professional teacher, in this era or future.